The interactive program for selection of the power cable by using Matlab software / Nor Azlina Mat Husin - Mat Husin, Nor Azlina (2005)
The conventional method in calculating cable ampacity is to calculate it under prescribed conditions and then to apply derating factors to cater for real conditions. Most of the power cable manufacturers use this method for designing power cables, which results in manufacturing cost. If we consider the real conditions (installation methods and operating conditions etc) in the calculation procedure, more accurate values can be obtained and it will help in the economic design of power cables. As this method involves complicated mathematical formulae, it is necessary to have a computer program to handle the calculation part. The program will handles this situation which was developed using MATLAB version 7.0. The program can calculate the ampacity of low voltage and medium voltage power cable lay in free air or directly buried in the ground. The user has to input the required data of the power cable design as well as the cable installation method to the program. The program can calculate the continuous current rating at rated load as well as the cyclic current rating according to specified load profile of the power cable. The calculation procedure is in accordance with International Electrotechnical Commission Standard of IEC 60502 and IEC 60287. It is provides solution to cables operating at a rated voltages of 36kV and below. It is a valuable tool for electrical engineers, consultants, academic staff and electrical engineering students.